Code-switching in teaching English subject for EFL students - I Gusti Agung Vony Purnama (English, 2020)
This study aims to find the types of code-switching employed by the lecturers in the teaching-learning process of EFL students and also to find the functions of the use of code-switching employed by the lecturers for teaching EFL students in ITB STIKOM Bali. The data source of this study was the interview transcribes of the lecturers who teach English subjects in ITB STIKOM Bali. They were interviewed regarding the use of code-switching in teaching EFL students. The theory of code-switching was used in this study and the results of the previous researches in the same areas were also used as the literature review. The finding shows that the situational and metaphorical types of code-switching were employed by the lecturer in the teaching-learning process. However, the situational type of code-switching was dominantly employed by the lecturers in the teaching-learning process. Another result was regarding the function of the code-switching that employed by the lecturer. It was found that the function of code-switching as a translation frequently employed by the lecturer. It is hoped this study can give information to the lecturer and teacher regarding the topic of code-switching.